Estimasi Jarak Genetik antar Domba Garut Tipe Tangkas dengan Tipe Pedaging - S S Mansjoer; T Kertanugraha; C Sumantri (Media Peternakan, 2007)
The objectives of the present study were to estimate the genetic distance and to determine the discriminant variables among fighting and meat types sheep of Garut (Garut sheep). A total of 413 heads of Garut sheep from five sub-populations were used in this study. Data were collected from the Regional Animal Research Center (BPPTD) as follows: 102 heads of common type sheep from Margawati (M), 69 heads from meat type sheep from Wanaraja (P), 72 heads of meat type from Sukawening (D), 81 heads of fighting sheep from Wanaraja (T) and 89 heads of fighting sheep from Sukawening (A). Data obtained were analyzed by simple discriminant with SAS package program version 7.0 and MEGA2 program to get the construction of phenogram tree. The results showed that in general fighting sheep had body weights and body measurements significantly higher (P < 0.05) than meat type sheep. However they were almost the same as common type sheep Margawati. The length and width of ears, tail width and chest width were the most discriminant variables to determine the differences of fighting type and meat type sheep. The highest similarities between individuals inside the group were obtained from Margawati common type sheep (71.57%), followed by Wanaraja meat type sheep (69.57%), Sukawening meat type sheep (69.44%), Wanaraja fighting type sheep (69.14%) and Sukawening fighting type sheep (59.55%). The Wanaraja fighting type sheep (T) had the closest genetic distance (1.16) to the Sukawening fighting type sheep (A), while the longest genetic distance (6.17) was between the Wanaraja meat type sheep and the Margawati common type sheep. The phenogram tree showed that the Margawati common type sheep was outside Wanaraja and Sukawening fighting type and meat type sheep, but the genetic distances were closer for the Wanaraja and Sukawening fighting type sheep. Key words: Garut sheep, genetic distance, body measurements